The protection of trade union funds and property - International Labour Office (Geneva : International Labour Office, 1960)
This is a report of the Committee on freedom of employers' and workers' organizations. It reveal that the question of reconciling the need to ensure that trade union funds are protected against misuse and the principle of trade union freedom from governmental interference constitutes a very real problem in a large number of countries and that the methods adopted in law and in practice with a view to its solution vary to a considerable degree.
Includes bibliographical references: p. [195]-200.
ahz 13/03/2019
Loans
Keywords: Labor unions; Industrial relations